Green Finance and CSR: Effects on Firm Value - Purwanti, Ari (West Science Accounting and Finance, 2024)
This study investigates the impact of sustainability reporting, green financing, corporate social responsibility (CSR), and environmental auditing on firm value and risk management in Indonesian manufacturing companies. Using a quantitative approach, data was collected from 100 manufacturing companies through a structured questionnaire based on a Likert scale. Data were analysed using SEM-PLS 3 to assess the relationship between variables. The findings show that all factors studied - sustainability reporting, green financing, CSR, and environmental auditing - positively and significantly influence firm value and enhance risk management practices. These results underscore the importance of integrating sustainable practices into corporate strategy to enhance firm value and effective risk management. The implications of these findings suggest that firms should prioritise sustainability initiatives as a key component of value creation and risk mitigation strategies in Indonesia's competitive manufacturing sector.